J'accuse - Gance, Abel; Hubert, Roger; Francen, Victor; Noro, Line; Gance, Sylvie (bfi, 2018)
Acclaimed as one of cinema's finest anti-war movies, Abel Gance's rousing indictment of warfare is as powerful and relevant today as it was on its original release in 1938. Having experienced the horror of the First World War, idealistic poet Jean Diaz (Victor Francen) turns to technology in a bid to prevent further barbarity. But a meddling and unscrupulous bureaucracy allows Jean's plans to be hijacked as Europe slides towards another great conflict. Using his epic 1919 silent version of the film as a template, Gance pits mankind's romanticism against its capacity for savagery. Originally released on the eve of the Second World War (and the same year as Jean Renoir's "La Grande Illusion"), "J'accuse" urges us to honour the memory of the fallen by learning the lessons of a catastrophic past. [www.amazon.co.uk]